Soil chemical properties to retain phosphorus in managed boreal peatlands in northern Finland - Höyhtyä, Iida; Ronkanen, Anna-Kaisa; Liimatainen, Maarit; Hyvärinen, Maarit; Kløve, Bjørn; Marttila, Hannu (Elsevier, 2025)
The drainage of peatlands increases peat decomposition, promoting the release of phosphorus (P) to soil pore water and the eventual leaching to water bodies. The P retention capacity in the soil layers affects the likelihood of subsequent P leaching to the drainage network. We aimed to study the retention patterns of P and to assess the risk of P leaching in the soil profiles of variably managed peatlands, including cultivated peatland of variable peat thickness, peatland forest, abandoned peat field, and pristine peatland in northern Finland. We studied the total concentrations of P and the P-sorbing elements iron (Fe), aluminum (Al), and calcium (Ca), P speciation in soil profiles using sequential chemical extraction, and the degree of P saturation (DPS) using ammonium oxalate extraction. Our results show that fertilization and peat decomposition have caused elevated element concentrations in cultivated sites. Other managed peatlands are rich in Fe and P, but poor in Ca compared to similar sites reported in the literature. In peat layers, P is mainly bound by organic compounds and Fe. Newly added P is likely retained by Fe and Al, although Ca-P still exists in mineral subsoils. We conclude that the heavy dependence on Fe in P sorption and low Fe:P and Al:P ratios indicate a potential of P leaching from decomposed peat when reducing conditions occur (e.g., due to water saturation), while a sufficient Al content may reduce P leaching in such conditions. Mineral subsoil above subsurface drainage has a higher P retention capacity than peat, though prevailing P saturation should be further studied in sites with a long fertilization history. Our results highlight the need to consider P leaching risk when planning peatland management and directly support the practical management of peatlands and water protection.
Keywords: managed peatland; phosphorus saturation degree; sequential chemical extraction; organic soil; water quality; phosphorus leaching